Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Simplify -2[9 - (x + 7)].

-32 - x
-4 - x
-4 + 2x
-32 + 2x


Sagot :

Answer: the real answer is =2x−4

Step-by-step explanation: −2(9−(x+7))

=(−2)(9+−x+−7)

=(−2)(9)+(−2)(−x)+(−2)(−7)

=−18+2x+14

=2x−4

Will it can be -4 + 2x, hope this help

jjjjjjjjjjjjjjjjjjjjjjjjjjjjjjjjjjj